2007
DOI: 10.1088/0029-5515/47/7/002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasma triangularity and collisionality on electron heat transport in TCV L-mode plasmas

Abstract: The impact of plasma shaping on electron heat transport is investigated in TCV L-mode plasmas. The study is motivated by the observation of an increase in the energy confinement time with decreasing plasma triangularity which may not be explained by a change in the temperature gradient induced by changes in the geometry of the flux surfaces. The plasma triangularity is varied over a wide range, from positive to negative values, and various plasmas conditions are explored by changing the total electron cyclotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
158
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(198 citation statements)
references
References 22 publications
(32 reference statements)
22
158
0
Order By: Relevance
“…In fact, Refs. [22][23][24][25] pointed out that core turbulence is (i) usually stabilised by elongation, except for large positive triangularities, for which it is enhanced, (ii) stabilised by negative triangularity, and (iii) destabilised by large positive triangularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Refs. [22][23][24][25] pointed out that core turbulence is (i) usually stabilised by elongation, except for large positive triangularities, for which it is enhanced, (ii) stabilised by negative triangularity, and (iii) destabilised by large positive triangularity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the effects of plasma shaping on core turbulence have been extensively studied, both experimentally and numerically (see, e.g., Refs. [22][23][24][25][26]), the attemps to study the effects of plasma shaping on SOL turbulence in limited geometry are only experimental (see, e.g., Ref. [27]).…”
Section: Introductionmentioning
confidence: 99%
“…This, too, has been investigated on TCV by analysis of integrated magnetic data. For both (3,2) and (2,1) mode excitation, it is found that a seed island forms within tens of μs of the sawtooth crash. The subsequent island development is consistent with the modified Rutherford equation.…”
Section: Ov/4-4mentioning
confidence: 98%
“…4b) [16]. This is a form of ELM mitigation in an alternative configuration not available to ITER, although it is accompanied by a worsening of confinement -in marked contrast with the L-mode regime, where confinement is better for δ<0 than for δ>0 [2].…”
Section: H-mode and Elmsmentioning
confidence: 99%
See 1 more Smart Citation